Enhancing Spiritual Well-Being in East Jakarta Through Community Service-Based Majelis Taklim: Meningkatkan Kesejahteraan Spiritual di Jakarta Timur Melalui Majelis Taklim Berbasis Pelayanan Masyarakat - Hamid, Abdul; Yuni, Badrah; Adnan, Mohammad (Yayasan Mata Pena Madani, 2025)
Spiritual well-being is an essential aspect of the life of urban people, especially in East Jakarta, which faces various social and economic challenges. This study explores the Majelis Taklim's role as a community service institution in improving the spiritual welfare of individuals in urban environments. Through a qualitative approach, this study involves semi-structured interviews and observations of participants and managers of the Majelis Taklim to understand the impact of religious activities on their spiritual lives. The study results show that the Majelis Taklim not only functions as a place for religious teaching but also as a forum for social interaction that strengthens solidarity and provides emotional support. Regular activities such as recitation and dhikr help participants find inner peace and meaning amid the busy city. Thus, the Majelis Taklim plays a strategic role in building the spiritual welfare of the people of East Jakarta, as well as offering opportunities to develop religious programs that are more adaptive to the needs of urban communities.